High efficiency Bi2Te3-based materials and devices for thermoelectric power generation between 100 and 300 °C. Issue 10 (19th September 2016) - Hao, Feng; Qiu, Pengfei; Tang, Yunshan; Bai, Shengqiang; Xing, Tong; Chu, Hsu-Shen; Zhang, Qihao; Lu, Ping; Zhang, Tiansong; Ren, Dudi; Chen, Jikun; Shi, Xun; et al.
Abstract : High efficiency Bi2 Te3 -based thermoelectric materials and devices with energy conversion efficiencies of up to 6.0% under a temperature gradient of 217 K. Abstract : By suppressing intrinsic excitation in p-type Bi2 Te3 -based materials, we report maximum and average zT values of up to 1.4 and 1.2 between 100 and 300 °C, respectively. Thermoelectric modules based on these high performance materials show energy conversion efficiencies of up to 6.0% under a temperature gradient of 217 K, and are greatly superior to current Bi2 Te3 -based modules.